Pengaruh Model Pembelajaran Kooperatif Tipe Number Head Together berbantuan Alat Praktikum Sederhana terhadap Penguasaan Konsep Siswa pada Materi Fluida Dinamis - Suci Fathul Ismi; Supriyatman; Syamsu (Universitas Tadulako, 2021)
This study aims to determine whether there is an effect of cooperative learning model Number Head Together with the aid of a simple practicum tool on students' mastery of dynamic fluid. This research is a quasi-experimental research using the equivalent pretest-posttest design. The instrument used is a test of mastery of physics concepts in the form of an essay test with 8 questions. The results of data processing, obtained the average pretest score of mastery of physics concepts for experimental class students was 9.75 while the average posttest score was 22.4. The control class obtained an average pretest score of 9.15 while the average posttest score was 18.6. The results of an average increase of 48.62% for each class are in the medium category with the n-gain value of the experimental class using the Number Head Together model with the help of a simple practicum tool is 56.17% while the control class using the Number Head Together model is 41.07%. Analysis of the test data was carried out using a one-party t-test statistical technique to test the difference in the mean score of mastery of physics concepts with a significant level of = 0.05. The results of one-party analysis determine that there is an influence of the Number Head Together model with the aid of a simple practicum tool on students' mastery of concepts in dynamic fluid materials